ASEAN Integration in the Context of Disaster Management - Arundhati, Gautama Budi; Ulum, Muhammad Bahrul; Afera, Gebrekiros Goytom (University of Jember, 2022)
The COVID-19 pandemic, a globally unprecedented disease outbreak, has alarmed all governments to reconsider the importance of disaster management policies at the domestic level. At the same time, handling transboundary disasters was another challenge faced by regional organizations such as the Association of Southeast Asian Nations (ASEAN). As a result of this pandemic, all member states tended to act more independently by closing their territories and isolating their citizens from cross-border migration. This paper aimed to examine ASEAN's existing measures to address the COVID-19 pandemic, following the importance of considering domestic policies taken by its member states to portray the possible action at the regional level. In practice, each ASEAN member state had various approaches, from strict lockdowns such as those implemented in Singapore to Indonesian policies that were far from being prepared. While COVID-19 is a non-natural disaster but has had a devastating impact on Southeast Asia, the future of regional integration is at stake. This paper showed that each member state's different social, economic, and political situations influenced the absence of early common practices at the domestic level to overcome this pandemic. Simultaneously, market stability in Southeast Asia was the key to regional development, whereas this pandemic harmed ASEAN's aim to meet economic integration. This paper suggested that ASEAN should establish guidelines regarding disaster management as experienced during the COVID-19 pandemic for member states' domestic policies to anticipate possible adverse episodes in the future that may hamper the integration progress.Keywords: ASEAN Integration, COVID-19, Disaster Management.